Influence of Dietary Energy and Poultry Fat on the Response of Broiler Chicks to Heat Therm - Ghazalah, A.A.; Abd-Elsamee, M.O.; Ali, A.M. (International Journal of Poultry Science, 2008)
Heat stress and the associated production losses and mortality are a challenge to commercial broiler production. A total number of 1000 one day old unsexed Arbor Acres broiler chicks were used in this study. Birds were offered with water and grower diet containing 23% crude protein and 3100 kcal ME/ kg of the diet from 1 to 4 weeks of age. At 29 day of age, 900 birds of nearly similar live body weight (about 850 g) were chosen to study the effect of different levels of metabolizable energy (ME) and poultry fat (PF) on broiler performance, nutrients digestibility and carcass characteristics during the hot summer season (29 - 36 °C and 50 - 60% H). The birds were randomly distributed into 9 treatments, each contained 100 birds in 4 replicates of 25 birds each. Three levels of ME and three levels of PF were tested in 3 X 3 factorial designs to alleviate the side effects of heat stress on broiler chick performance. The tested ME levels (kcal/ kg) were 3100 (low level, ME1), 3200 (recommended level, ME2) and 3300 (high level, ME3). The tested three levels of PF were 0 % (PF1), 2.5% (PF2) and 5% (PF3) for each level of ME. Chicks were allocated in a littered floor poultry house in an open system under the same management conditions. Water and feed were offered ad-libitum and artificial lighting was provided 24 hours daily for the either experimental period, which lasted for 7 weeks.The overall results showed that the average body weight, body weight gain, feed conversion ratio and performance index were improved significantly with high levels of either metabolizable energy or poultry fat. Data showed that the digestion coefficient of both crude protein and ether extract were improved significantly when broiler chicks were fed diets containing high level of either metabolizable energy or poultry fat. Results indicated that the average values of abdominal fat increased significantly with high levels of either metabolizable energy or poultry fat. While, there were no significant differences for either dressing percentage or giblets due to dietary treatments. Therefore, it is suggested to increase dietary metabolizable energy more than recommended level and adding fat up to 5 % of the diet to alleviate the side effects of heat stress on the performance of broiler chicks.